Single Cell RNA Sequencing Reveals Deep Homology of Dental Cell Types Across Vertebrates - Gruenhagen, George W.; Mubeen, Talha; Patil, Chinar; Stockert, Joseph; Streelman, Jeffrey T. (Frontiers in Dental Medicine, 2022)
Like most mammals, humans replace their teeth once throughout their lives and have limited regenerative capabilities. In contrast, mice continually renew tissues lost due to gnawing through a well characterized population of stem cells on the labial surface of the incisor. Most non-mammalian vertebrates replace teeth throughout life; the cellular and molecular mechanisms of successional tooth replacement are largely unknown. Here we use single nuclei RNA sequencing (snRNA-seq) of replacement teeth and adjacent oral lamina in Lake Malawi cichlids, species with lifelong whole-tooth replacement, to make two main discoveries. First, despite hundreds of millions of years of evolution, we demonstrate conservation of cell type gene expression across vertebrate teeth (fish, mouse, human). Second, we used an approach that combines marker gene expression and developmental potential of dental cells to uncover the transcriptional signature of stem-like cells in regenerating teeth. Our work underscores the importance of a comparative framework in the study of vertebrate oral and regenerative biology.